Comparative Performance of Material Extrusion and Vat Photopolymerization Systems for Automotive Product - Tanoto, Yopi Yusuf; Sugiarto, Nicholas Adriel; Hernando, Ivan Christian; Anggono, Willyanto (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2025)
Additive Manufacturing (AM) has emerged as a rapidly developing technology with applications ranging from product visualization and prototype fabrication to actual production. Various types of AM are available on the market, broadly categorized into industrial-grade and consumer-grade machines. This study focuses on consumer-grade printers, which are more affordable and widely accessible. Among these, the two most commonly used technologies are Material Extrusion (ME) and Vat Photopolymerization (VP). While the performance of ME printers has been widely investigated, comparative studies between ME and VP remain limited. This research provides a performance comparison of the two technologies. The findings indicate that VP printers outperform ME in terms of printing speed and energy efficiency. On the other hand, FDM printers offer advantages in material cost and dimensional accuracy in the Z direction. Furthermore, the study examines the potential of consumer-grade printers to support automotive product prototyping efficiently and practically.